Estabelecimento de indicadores da qualidade da água e do solo: uma construção ao nível de agroecossistema familiar e de base ecológica - Almeida, Manoela Terra de (2013)
This research was developed in a family ecological agroecosystem, in Morro Redondo / RS. The objective was to evaluate the performance of physical, chemical and biological soil and water indicators. And from this, constructing and proposing a minimum set of indicators to use as a reference in assessing the sustainability of the studied agroecosystem. Given the above, using the multivariate analysis, it was identified a minimum data set of soil and water indicators: macroporosity, bulk density, aluminum, cation exchange capacity, earthworms, microbial nitrogen, respiration, organic carbon, nitrate and thermotolerant coliform The potential use of this data set for developing sustainable land management is discussed in this research.